(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
In the article the British Treasury borrowing Ukrainian terminology. Traced function internationalism and kalok English origin. Zaktsentovano attention to the appropriate use of borrowing.